Good faith collaboration the culture of Wikipedia - Reagle, Joseph Michael (MIT Press, 2010)
Wikipedia, the online encyclopedia, is built by a community - a community of Wikipedians who are expected to "assume good faith" when interacting with one another. In Good Faith Collaboration, Joseph Reagle examines this unique collaborative culture.
Keywords: Wikipedia.; Electronic encyclopedias -- Case studies.; Wikis (Computer science) -- Case studies.; Communication in learning and scholarship -- Technological innovations -- Case studies.; Authorship -- Collaboration -- Case studies.; Online social networks -- Case studies.; elektronické knihy; electronic books